Avaliação do uso de armadilhas de oviposição como método de vigilância entomológica para Aedes aegypti - Barbosa, Angelita Anália Carniel (2006)
Oviposition traps are considered important entomological surveillance tools for Aedes aegypti, although they are still not used in routine activities of the Dengue Control Program in Brazil. The aims of this study were to evaluate the behavior of oviposition traps and related them to larval density measures and climatic data. This study was performed in a quarter from São José do Rio Preto, state of São Paulo, where fifty blocks were selected and two houses in opposite sides of each block were chosen to have the traps installed. A trap was installed at unshaded outdoor sites in each house, next to plants and in a height ranging from 0,5m to 1m. A measure was made each fifteen days, from October 2003 to September 2004, with the installation of the oviposition traps in the first week and the removal of them at the second week. Larval density measures were performed each fifteen days and climatic data was obtained on daily basis. The method of Generalized Estimation Equation was used to adjust the models among the positivity, the mean number of eggs and the other analyzed variables. Three distinct periods were identified at the positivity behavior of the oviposition traps and the mean number of obtained eggs. At the first (October to November), there was an increase in the values; at the second (January to May), the values remained stable; and at the third (June to September), there was a decrease. The observed values of positivity and the mean number of eggs observed at the first and third periods followed the variations in climatic data. From October to December, high correlations were obtained between the positivity and mean number of eggs, showing that one variable predicts the other and, at this period, the mean number of eggs can be estimated just by the positivity. The adjusted models for the positivity and mean number of eggs had temperature, humidity, pluviosity and fortnight as explicative variables. They also indicated the possibility of obtaining predictive models in a way these measures could be estimated without the necessity of fieldwork activities. For both models, the larval density measure was not included as an explicative variable. The trap presented a sensibility to detect Aedes aegypti higher than 90% and the larval density measures were always inferior to 25%. The periods from October to December and June to September were identified as the most appropriate to use oviposition traps as entomological surveillance tools. The period from December to June was identified as the ideal time to perform larval density measures.